Identification of Novel phoP-phoQ Regulated Genes that Contribute to Polymyxin B Tolerance in Pseudomonas aeruginosa - Yang, Baopeng (Microorganisms, 2021)
Polymyxin B and E (colistin) are the last resorts to treat multidrug-resistant Gram-negative pathogens. Pseudomonas aeruginosa is intrinsically resistant to a variety of antibiotics. The PhoP-PhoQ two-component regulatory system contributes to the resistance to polymyxins by regulating an arnBCADTEF-pmrE operon that encodes lipopolysaccharide modification enzymes. To identify additional PhoP-regulated genes that contribute to the tolerance to polymyxin B, we performed a chromatin immunoprecipitation sequencing (ChIP-Seq) assay and found novel PhoP binding sites on the chromosome. We further verified that PhoP directly controls the expression of PA14_46900, PA14_50740 and PA14_52340, and the operons of PA14_11970-PA14_11960 and PA14_52350-PA14_52370. Our results demonstrated that mutation of PA14_46900 increased the bacterial binding and susceptibility to polymyxin B. Meanwhile, mutation of PA14_11960 (papP), PA14_11970 (mpl), PA14_50740 (slyB), PA14_52350 (ppgS), and PA14_52370 (ppgH) reduced the bacterial survival rates and increased ethidium bromide influx under polymyxin B or Sodium dodecyl sulfate (SDS) treatment, indicating roles of these genes in maintaining membrane integrity in response to the stresses. By 1-N-phenylnaphthylamine (NPN) and propidium iodide (PI) staining assay, we found that papP and slyB are involved in maintaining outer membrane integrity, and mpl and ppgS-ppgH are involved in maintaining inner membrane integrity. Overall, our results reveal novel PhoP-PhoQ regulated genes that contribute to polymyxin B tolerance.